2018
DOI: 10.1364/boe.9.003220
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning based segmentation of the optic nerve head using multi-contrast Jones matrix optical coherence tomography with semi-automatic training dataset generation

Abstract: A pixel-by-pixel tissue classification framework using multiple contrasts obtained by Jones matrix optical coherence tomography (JM-OCT) is demonstrated. The JM-OCT is an extension of OCT that provides OCT, OCT angiography, birefringence tomography, degree-of-polarization uniformity tomography, and attenuation coefficient tomography, simultaneously. The classification framework consists of feature engineering, -means clustering that generates a training dataset, training of a tissue classifier using the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Machine learning techniques have been explored to segment microvasculature, 166 non-perfusion areas, 167 optical nerve head. 168 A support vector machine (SVM) classifier was recently demonstrated for supervised machine learning based OCTA classification of SCR 35 and DR. 39 Six OCTA features, i.e. BVD, BVC, BVT, VPI, FAZ-A, and FAZ-CI, were used to train the SVM classifier for identifying control, mild, and severe SCR subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning techniques have been explored to segment microvasculature, 166 non-perfusion areas, 167 optical nerve head. 168 A support vector machine (SVM) classifier was recently demonstrated for supervised machine learning based OCTA classification of SCR 35 and DR. 39 Six OCTA features, i.e. BVD, BVC, BVT, VPI, FAZ-A, and FAZ-CI, were used to train the SVM classifier for identifying control, mild, and severe SCR subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning, and other advanced computational techniques have begun to dramatically reduce the time taken to convert an imaged volume to discrete and quantifiable structures within the volume (Januszewski et al, 2018; Berning et al, 2015; Lucchi et al, 2010; Meijs et al, 2017; Camacho et al, 2018; Kasaragod et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Both collagen beams and neural tissues are highly scattering, and previous studies have shown that collagen beams are more scattering than neural tissues. 23 The neural tissues appear to have similar properties to white matter, which has weak absorption and the collagen tissues were also reported to have weak absorption. 24,25 To compare the performance of SPLM on thick tissues with regular PLM on thin sections, we fixed and cryosectioned coronally (transversely) a sheep ONH starting from the anterior side.…”
Section: Sample Preparation and Mountingmentioning
confidence: 99%